Studi Pemanfaatan Limbah Beton Mutu Tinggi pada Campuran Asphalt Concrete Binder Course (AC-BC) - Ika Sulianti (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
The purpose of this research is to find out whether the modification of asphalt used with high quality of concrete waste as coarse substitute aggregate of Asphalt Concrete - Binder Course (AC – BC). In this study, the researcher used high quality of concrete waste fc’ 42, fc’ 47, fc’ 50, each waste concrete quality will be mixed with asphalt bitumen contents 5%, 5.5 %, 6 %, 6.5, and 7%. This research used the Marshall test method to determine stability value, flow value, Void In Mix (VIM), Void In Mineral Aggregate (VMA), Void Filled With Asphalt (VFA). AC - BC with high quality of concrete waste fc'42 obtained for the best bitumen content obtained is 7%, with a stability value of 1491.705 kg, flow 4.264 mm, MQ 343.465, VIM 9.190%, VFA 34.425%, VMA 15.067%. AC - BC with high quality of concrete waste fc'47 was obtained for the best asphalt content obtained was 7%, with stability values ​​1551.715 kg / mm, flow 4.587 mm, MQ 339.122, VIM 5.530%, VFA 63.308%, VMA 14.235%.The best results of the Marshall test were obtained at the high quality of concrete waste fc'50, asphalt content obtained is 7%, with the stability of 1616.145 kg, flow 4.859 mm, MQ 333.720, VIM 5.116%, VFA 55.597%, VMA 13.226%. Referring to the obtained research test, the values of stability match with Bina Marga standard value, namely 800 kg, but VFA value, VIM, and flow are not of Bina Marga standard values. In addition, VMA vales fulfilling Bina Marga standard values are concrete waste fc’42 and fc’47 with the scale 14%. The researcher hopes that this research will be the guideline in making a mixture of asphalt concrete binder courses with the replacement of coarse aggregate using concrete waste and to inspire people in utilizing concrete waste in technical aspects.